CRITICAL ANALYSIS BUILDING THE QUALITY OF ISLAMIC UNIVERSITY IN THE WORLD OF WORK - Anggun, Dewi; Lestari, Fani Dwi; Damayanti, Nurmalita; Amrillah, Rizki (STAI Asy-Syukriyyah, 2024)
This research aimed to critically understand how to build the quality of Islamic university graduates and the needs of the world of work. Researchers used qualitative research with the type of library research to implement the method in this research. The research results showed that there was a gap between the skills taught in universities and those needed in the workplace. Therefore, it was necessary to strengthen soft skills and hard skills while students were studying at university. At this point, Islamic universities needed to actualize their curriculum system by basing it on the needs of the realities of the contemporary world of work. These findings provided an important contribution for Islamic universities and industry to increase their collaboration in preparing professional graduates who were more ready to work in order to meet the quality of civilization of the next generation of the nation.